Enhancing Teacher Excellence: The Impact of Competency and Work Facilities Mediated by Work Achievement - Yanthi, Komang Ovi Arinda; Adnyana, I Putu Agus (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the influence of competence and work facilities on teacher performance through job achievement as an intervening variable among teachers at SMP Negeri 8 Singaraja. The data analysis technique used is Structural Equation Modeling (SEM) based on variance, known as Partial Least Square (PLS) version 3.0. The results indicate that competence has a positive and significant effect on teacher performance, suggesting that higher competence leads to better performance. Work facilities also show a positive and significant impact on performance, implying that adequate facilities help teachers optimize their work. Additionally, competence positively affects job achievement, indicating that competent teachers are more likely to improve their achievements. Work facilities likewise significantly enhance job achievement by supporting teaching activities. Finally, job achievement has a positive and significant effect on teacher performance, confirming that higher achievement leads to better overall performance.